Value Co-Creation Dimensions: Their Effect On Satisfaction Of Cooperative Members - Yusman, Yacob; Jati Kasuma, Ali; Hiram, Ting (MKM & KPDNKK, 2016)
Value co-creation is a crucial component in the service industry and pivotal to the growth and survival of organizations. The rationale is based on the belief that value is created by both the organizations and the customers. Notwithstanding its magnitude, little is done to delve into the subject matter in cooperatives in the context of developing markets. The present study attempts to investigate the relationship between value co-creation dimensions and satisfaction of cooperative members in Sarawak. A quantitative approach using self-administered survey was adopted. A total of 300 copies of the questionnaire were distributed to cooperative members in Sarawak and 274 usable copies were subsequently collected. Multiple regressions analysis was conducted to assess the effect of value co-creation dimensions on members’ satisfaction. The findings indicate that relating, ethical, developmental and concerted joint actions have positive effect on members’ satisfaction, where developmental joint actions is found to be the strongest influence dimension. The study thus highlights the practical importance of learning culture among service providers and cooperative members, and lays the foundation for future studies.